The role of financial analysis in evaluating the performance of industrial enterprises to predict financial failure - AL- Kassar, Talal; Kouachi, Mourad; Nasruldeen, Ammar (Journal of Human Sciences, 2016)
This study aimed to describe the effects of the financial analysis to predict the financial failure of enterprises through using of financial ratios. Also to build a model consisting of a set of financial ratios through of their weight. It reflects the extent of its importance in predicting the failure of industrial enterprises and success. This can take appropriate action to avoid financial failure before it happens. The main results of the study, reaching is four financial ratios explain and predict financial performance individually. These are a ratio of current assets to total assets, ratio of debtors to sales, ratio of net profit before interest and tax to current liabilities, and ratio of the market value of capital-to-book value of the total debt. The last one was the most important ratio. The model consists of three financial ratios are the strongest influence through statistical analysis of financial ratios. This model was able to re-rating of food enterprises successful and failed fully and accurately by (100%). It was able to distinguish between successful enterprises and failed in another sample from the same sector by (90%) and therefore, the accuracy of this model is very high, and reliable. The model showed that it does not need many financial ratios to be able to predict the failure of the financial performance of enterprises. That with the advancement of statistical analysis methods remains discriminatory analysis statistical tool is very effective, and reliable.